ASSESSMENT OF THE EFFECTIVENESS OF MANAGEMENT OF BUSINESS PROCESSES OF AN ORGANIZATION IN THE CONTEXT OF DIGITALIZATION (Educa Journal of Studies, 2026)
The article discusses the issues of assessing the effectiveness of business process management of organizations in the context of digitalization. The features of digital platforms, their impact on flexibility, automation and integration of processes, as well as the possibilities of increasing productivity and reducing errors are analyzed. The dependence of the effectiveness of digital management on the technological infrastructure, the competence of employees and compliance with the strategic goals of the organization is shown. methodological approaches to monitoring and evaluating the effectiveness of business processes, including quantitative and qualitative indicators. The work allows you to formulate recommendations for the implementation of digital management models to increase the competitiveness of the organization.
Keywords: Digitalization, digital platforms, business processes, management, efficiency, automation, monitoring, integration, KPI, organizational adaptation.